Collaborating for Improved Delivery of Health Care Services in the Horse Racing Industry: A University Interdisciplinary Program - Whitney A. Nash; Rhonda D. Buchanan (The University of Alabama, 2022)
This research describes the collaboration between the University of Louisville School of Nursing, the Latin and Latino Studies Program, and the Kentucky Racing Health and Welfare Fund to provide low to no cost comprehensive health care services to the backside workers (behind the scenes) in the thoroughbred horse racing industry. An integral part of this program is the Latin American and Latino Studies (LALS) internship, which provides students the opportunity to fulfill their requirement while providing a much-needed service to the racing industry's primarily Hispanic population. Students complete a semester-long internship that enables them to refine their translation/interpretation skills in Spanish while developing a broader understanding of the impact of cultural determinants of health. Students have reported the experience to be professionally and personally rewarding and have identified it as "life-changing."